1998
DOI: 10.1002/jlb.64.4.467
|View full text |Cite
|
Sign up to set email alerts
|

P-selectin and MAC-1 mediate monocyte rolling and adhesion to ECM-bound platelets under flow conditions

Abstract: Accumulation of monocyte-derived foam cells in focal areas of the atherosclerotic (A.S.-) lesion is one of the key events in early atherogenesis. Using a flow model for the damaged vessel wall, we examined the ability of ECM-bound platelets to induce monocyte tethering and adhesion. Whereas ECM-proteins alone induced monocyte adhesion only at low shear stresses (F100 mPa), ECM-bound platelets induced monocyte rolling and adhesion at shear stresses up to 240 mPa. Studies with specific antibodies showed that mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 45 publications
4
48
0
2
Order By: Relevance
“…Similar results were found on atherosclerotic endothelium (25), on which VCAM-1 is also highly expressed. In an in vitro model of monocyte adhesion to the injured vessel wall, Kuijper et al (26) found that Mac-1 is the predominant integrin mediating monocyte rolling on ECM alone and that the interaction of PSGL-1 with P-selectin as well as Mac-1 accounts for nearly all the rolling interactions on activated platelets bound to ECM substrates at low shear stress.…”
Section: Leukocyte Recruitmentmentioning
confidence: 99%
“…Similar results were found on atherosclerotic endothelium (25), on which VCAM-1 is also highly expressed. In an in vitro model of monocyte adhesion to the injured vessel wall, Kuijper et al (26) found that Mac-1 is the predominant integrin mediating monocyte rolling on ECM alone and that the interaction of PSGL-1 with P-selectin as well as Mac-1 accounts for nearly all the rolling interactions on activated platelets bound to ECM substrates at low shear stress.…”
Section: Leukocyte Recruitmentmentioning
confidence: 99%
“…[1][2][3] After endothelial denudation, exposure of the basement membrane and subendothelial matrix leads to the deposition of fibrin and adherent platelets, which on activation and degranulation express P-selectin and present fibrinogen, thereby mediating leukocyte rolling and arrest, and supporting their inflammatory recruitment. 4,5 Because of secretion of cytokines or growth factors, monocyte-derived macrophages may be associated with lesion progression, including the proliferation of migrated smooth muscle cells. 2 The increase in neointima is accompanied by a reendothelialization, which is usually completed after 3 weeks.…”
mentioning
confidence: 99%
“…In accordance, we found a comparable effect of platelet coverage on monocyte adhesion. 24 More platelets and thus P-selectin presence only lowers rolling velocity. Lawrence et al 25 reported a similar decrease in rolling velocity when more purified P-selectin was coated on coverslips.…”
Section: Discussionmentioning
confidence: 99%